2012
DOI: 10.1016/j.acap.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving Clinician Self-Efficacy Does Not Increase Asthma Guideline Use by Primary Care Clinicians

Abstract: Objectives The association between changes in clinician self-efficacy and readiness to change and implementation of an asthma management program (Easy Breathing©) was examined. Methods A 36 month randomized, controlled trial was conducted involving 24 pediatric practices (88 clinicians). Randomized clinicians received interventions designed to enhance clinician self-efficacy and readiness to change which were measured at baseline and 3 years. Interventions consisted of an educational toolbox, seminars, telec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…75 The pre-post studies reported increases in the provision of action plans (27%-46%). [76][77][78]88 Both RCTs reported nonsignificant increases in patient education/asthma action plans (7% in 1 study; relative risk = 1.82 in the other study).…”
Section: Multicomponentmentioning
confidence: 99%
See 3 more Smart Citations
“…75 The pre-post studies reported increases in the provision of action plans (27%-46%). [76][77][78]88 Both RCTs reported nonsignificant increases in patient education/asthma action plans (7% in 1 study; relative risk = 1.82 in the other study).…”
Section: Multicomponentmentioning
confidence: 99%
“…Of the 6 studies we reviewed, 73,[75][76][77][78]88 most included an educational component but also included (1) training in communication techniques with provision of a spirometer and training in use of the spirometer 76 ; (2) laminated posters of guidelines and medications with feedback on asthma action plan use and monthly calls from an intervention team to troubleshoot communication problems 88 ; (3) asthma kits (peak flow meters, spacers, educational materials) and systems-level changes (flow sheets and standing medication orders) 73 ; (4) systematic use of a patient questionnaire and an asthma management algorithm 77 ; (5) an asthma coordinator and feedback on performance as part of continuous quality improvement efforts; or (6) an educational toolbox with seminars, teleconferences, mini fellowships, opinion leader visits, clinician-specific feedback, and pay for performance. 75 The pre-post studies reported increases in the provision of action plans (27%-46%).…”
Section: Multicomponentmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps combining our work with that of Cloutier et al, 62 who were able to improve pediatricians' readiness to change, would reduce this barrier.…”
Section: Discussionmentioning
confidence: 99%